Bimanual Microincision Cataract Surgery versus Coaxial Microincision Cataract Surgery: A Meta-Analysis of Randomized Controlled Trials and Cohort Studies - Fu, Chenxi (J Ophthalmol, 2017)
PURPOSE: This meta-analysis was conducted to compare the intraoperative and postoperative outcomes of bimanual microincision cataract surgery (B-MICS) and coaxial microincision cataract surgery (C-MICS). METHODS: Three databases were searched for papers that compared B-MICS and C-MICS from inception to June 2016. The following intraoperative and postoperative outcomes were included in the final meta-analysis: ultrasound time (UST), effective phacoemulsification time (EPT), balanced salt solution use (BSS use), mean surgery time, best-corrected visual acuity (BCVA), central corneal thickness (CCT), and increased CCT. RESULTS: There were no statistically significant differences in mean surgery time, UST, BSS use, BCVA, CCT, or increased CCT (one subgroup at postoperative day 7-8 and another subgroup at postoperative day 30). However, there was less EPT needed during surgery (p < 0.01) and lower levels of increased CCT at postoperative day 1 (p = 0.02) in the B-MICS group compared with the C-MICS group. CONCLUSIONS: The EPT was shorter and increased CCT was less at postoperative day 1 in the B-MICS group. There were no statistically significant differences in other intraoperative and postoperative outcomes between the B-MICS group and the C-MICS group. B-MICS is an efficient and safe cataract surgery procedure.